Key Factors in the Application of Sharestart to Enhance the Learning Attitude of Students - Luo, Yu-Zhou; Fang, Zhen; Sun, Long-Jie; Zhu, Jie (Frontiers in Psychology, 2021)
Under the background of globalization and the popularity of distance learning and e-learning channels provided on the Internet, teaching methods to encourage students’ self-directed learning are becoming popular. There are increasing domestic teachers joining in the practice for change. Various teaching methods that make the students acquire critical thinking skills; can be summarized as learning by doing, critical thinking learning, multiple assessments, team discussion teaching, and cooperative learning. Aiming at teachers of universities in Shanghai as the questionnaire analysis objects, total 360 copies of questionnaire are distributed, and 256 valid copies are retrieved, with the retrieval rate 71％. The research results are summarized as followings. 1. “Students’ mental adaptation and engagement” is the most emphasized dimension, followed by “teachers’ professional development”, “administration and parent support”, and “material and teaching strategy”. 2. Top five emphasized indicators, among 14, are ordered cultivation of self-study and thinking habits, development of professional community for teachers’ collaborative lesson study, support and cooperation of president and administration, adoption of heterogeneous grouping, and co-learning and discussion and cooperative learning. According to the results to propose suggestions, it is expected to propose more definite practice directions for teachers intending to attempt such a teaching method as well as provide some specific suggestions for first movers of Sharestart.